Question and Answers Forum

All Questions      Topic List

Mensuration Questions

Previous in All Question      Next in All Question      

Previous in Mensuration      Next in Mensuration      

Question Number 186924 by Mingma last updated on 12/Feb/23

Answered by mr W last updated on 12/Feb/23

Commented by mr W last updated on 12/Feb/23

cos α=((s^2 +c^2 −a^2 )/(2sc))  cos γ=((4s^2 +c^2 −d^2 )/(4sc))  γ=(π/3)−α  ((4s^2 +c^2 −d^2 )/(4sc))=(1/2){((s^2 +c^2 −a^2 )/(2sc))+((√(3[2(3c^2 −a^2 )s^2 −(c^2 −a^2 )^2 −s^4 ]))/(2sc))}  3s^2 −d^2 +a^2 =(√(3[2c^2 s^2 −s^4 −c^4 +2(s^2 +c^2 )a^2 −a^4 ]))  4a^4 −2(3c^2 +d^2 )a^2 +12s^4 −6(c^2 +d^2 )s^2 +3c^4 +d^4 =0  roots of this eqn. are a^2  and b^2 .  a^2 +b^2 =((2(3c^2 +d^2 ))/4)=((3c^2 +d^2 )/2)  that means there is following   correlation between a,b,c,d:   determinant (((2(a^2 +b^2 )=3c^2 +d^2 )))  a^2 b^2 =((12s^4 −6(c^2 +d^2 )s^2 +3c^4 +d^4 )/4)  s^4 −(((c^2 +d^2 )s^2 )/2)+((3c^4 +d^4 −4a^2 b^2 )/(12))=0  s^2 =(1/4)[c^2 +d^2 +(√((16a^2 b^2 −(3c^2 −d^2 )^2 )/3))]  ⇒s=(1/2)(√(c^2 +d^2 +(√((16a^2 b^2 −(3c^2 −d^2 )^2 )/3))))  in current case:  a=5, c=8, d=10  5^2 +b^2 =((3×8^2 +10^2 )/2)  ⇒b^2 =((3×8^2 +10^2 )/2)−5^2 =121  ⇒b=(√(121))=11

$$\mathrm{cos}\:\alpha=\frac{{s}^{\mathrm{2}} +{c}^{\mathrm{2}} −{a}^{\mathrm{2}} }{\mathrm{2}{sc}} \\ $$$$\mathrm{cos}\:\gamma=\frac{\mathrm{4}{s}^{\mathrm{2}} +{c}^{\mathrm{2}} −{d}^{\mathrm{2}} }{\mathrm{4}{sc}} \\ $$$$\gamma=\frac{\pi}{\mathrm{3}}−\alpha \\ $$$$\frac{\mathrm{4}{s}^{\mathrm{2}} +{c}^{\mathrm{2}} −{d}^{\mathrm{2}} }{\mathrm{4}{sc}}=\frac{\mathrm{1}}{\mathrm{2}}\left\{\frac{{s}^{\mathrm{2}} +{c}^{\mathrm{2}} −{a}^{\mathrm{2}} }{\mathrm{2}{sc}}+\frac{\sqrt{\mathrm{3}\left[\mathrm{2}\left(\mathrm{3}{c}^{\mathrm{2}} −{a}^{\mathrm{2}} \right){s}^{\mathrm{2}} −\left({c}^{\mathrm{2}} −{a}^{\mathrm{2}} \right)^{\mathrm{2}} −{s}^{\mathrm{4}} \right]}}{\mathrm{2}{sc}}\right\} \\ $$$$\mathrm{3}{s}^{\mathrm{2}} −{d}^{\mathrm{2}} +{a}^{\mathrm{2}} =\sqrt{\mathrm{3}\left[\mathrm{2}{c}^{\mathrm{2}} {s}^{\mathrm{2}} −{s}^{\mathrm{4}} −{c}^{\mathrm{4}} +\mathrm{2}\left({s}^{\mathrm{2}} +{c}^{\mathrm{2}} \right){a}^{\mathrm{2}} −{a}^{\mathrm{4}} \right]} \\ $$$$\mathrm{4}{a}^{\mathrm{4}} −\mathrm{2}\left(\mathrm{3}{c}^{\mathrm{2}} +{d}^{\mathrm{2}} \right){a}^{\mathrm{2}} +\mathrm{12}{s}^{\mathrm{4}} −\mathrm{6}\left({c}^{\mathrm{2}} +{d}^{\mathrm{2}} \right){s}^{\mathrm{2}} +\mathrm{3}{c}^{\mathrm{4}} +{d}^{\mathrm{4}} =\mathrm{0} \\ $$$${roots}\:{of}\:{this}\:{eqn}.\:{are}\:{a}^{\mathrm{2}} \:{and}\:{b}^{\mathrm{2}} . \\ $$$${a}^{\mathrm{2}} +{b}^{\mathrm{2}} =\frac{\mathrm{2}\left(\mathrm{3}{c}^{\mathrm{2}} +{d}^{\mathrm{2}} \right)}{\mathrm{4}}=\frac{\mathrm{3}{c}^{\mathrm{2}} +{d}^{\mathrm{2}} }{\mathrm{2}} \\ $$$${that}\:{means}\:{there}\:{is}\:{following}\: \\ $$$${correlation}\:{between}\:{a},{b},{c},{d}: \\ $$$$\begin{array}{|c|}{\mathrm{2}\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} \right)=\mathrm{3}{c}^{\mathrm{2}} +{d}^{\mathrm{2}} }\\\hline\end{array} \\ $$$${a}^{\mathrm{2}} {b}^{\mathrm{2}} =\frac{\mathrm{12}{s}^{\mathrm{4}} −\mathrm{6}\left({c}^{\mathrm{2}} +{d}^{\mathrm{2}} \right){s}^{\mathrm{2}} +\mathrm{3}{c}^{\mathrm{4}} +{d}^{\mathrm{4}} }{\mathrm{4}} \\ $$$${s}^{\mathrm{4}} −\frac{\left({c}^{\mathrm{2}} +{d}^{\mathrm{2}} \right){s}^{\mathrm{2}} }{\mathrm{2}}+\frac{\mathrm{3}{c}^{\mathrm{4}} +{d}^{\mathrm{4}} −\mathrm{4}{a}^{\mathrm{2}} {b}^{\mathrm{2}} }{\mathrm{12}}=\mathrm{0} \\ $$$${s}^{\mathrm{2}} =\frac{\mathrm{1}}{\mathrm{4}}\left[{c}^{\mathrm{2}} +{d}^{\mathrm{2}} +\sqrt{\frac{\mathrm{16}{a}^{\mathrm{2}} {b}^{\mathrm{2}} −\left(\mathrm{3}{c}^{\mathrm{2}} −{d}^{\mathrm{2}} \right)^{\mathrm{2}} }{\mathrm{3}}}\right] \\ $$$$\Rightarrow{s}=\frac{\mathrm{1}}{\mathrm{2}}\sqrt{{c}^{\mathrm{2}} +{d}^{\mathrm{2}} +\sqrt{\frac{\mathrm{16}{a}^{\mathrm{2}} {b}^{\mathrm{2}} −\left(\mathrm{3}{c}^{\mathrm{2}} −{d}^{\mathrm{2}} \right)^{\mathrm{2}} }{\mathrm{3}}}} \\ $$$${in}\:{current}\:{case}: \\ $$$${a}=\mathrm{5},\:{c}=\mathrm{8},\:{d}=\mathrm{10} \\ $$$$\mathrm{5}^{\mathrm{2}} +{b}^{\mathrm{2}} =\frac{\mathrm{3}×\mathrm{8}^{\mathrm{2}} +\mathrm{10}^{\mathrm{2}} }{\mathrm{2}} \\ $$$$\Rightarrow{b}^{\mathrm{2}} =\frac{\mathrm{3}×\mathrm{8}^{\mathrm{2}} +\mathrm{10}^{\mathrm{2}} }{\mathrm{2}}−\mathrm{5}^{\mathrm{2}} =\mathrm{121} \\ $$$$\Rightarrow{b}=\sqrt{\mathrm{121}}=\mathrm{11} \\ $$

Commented by Mingma last updated on 12/Feb/23

Excellent

Answered by nikif99 last updated on 12/Feb/23

In orthogonal yAx:  Eq. of circle (A, r=5) at point K: K_x ^2 +K_y ^2 =5^2  (1)  Eq. of (B, r=8) at K: (K_x −B_x )^2 +(K_y −B_y )^2 =8^2  ⇒  [K_x −(−(a/2))]^2 +(K_y −((a(√3))/2))^2 =64⇒  a(a+K_x −(√3)K_y )=39 (2)  Eq. of (K, r=10) at E: (E_x −K_x )^2 +(E_y −K_y )^2 =10^2  ⇒  (a+(a/2)−K_x )^2 +(((a(√3))/2)−K_y )^2 =100 ⇒  a(3a−3K_x −(√3)K_y )=75 (3)  (1)(2)(3) ⇒a=8.357297  K_x =3.101745, K_y =3.921629  CK=(√((K_x −C_x )^2 +(K_y −C_y )^2 )) ⇒CK=11

$$\underline{{In}\:{orthogonal}\:{yAx}:} \\ $$$${Eq}.\:{of}\:{circle}\:\left({A},\:{r}=\mathrm{5}\right)\:{at}\:{point}\:{K}:\:{K}_{{x}} ^{\mathrm{2}} +{K}_{{y}} ^{\mathrm{2}} =\mathrm{5}^{\mathrm{2}} \:\left(\mathrm{1}\right) \\ $$$${Eq}.\:{of}\:\left({B},\:{r}=\mathrm{8}\right)\:{at}\:{K}:\:\left({K}_{{x}} −{B}_{{x}} \right)^{\mathrm{2}} +\left({K}_{{y}} −{B}_{{y}} \right)^{\mathrm{2}} =\mathrm{8}^{\mathrm{2}} \:\Rightarrow \\ $$$$\left[{K}_{{x}} −\left(−\frac{{a}}{\mathrm{2}}\right)\right]^{\mathrm{2}} +\left({K}_{{y}} −\frac{{a}\sqrt{\mathrm{3}}}{\mathrm{2}}\right)^{\mathrm{2}} =\mathrm{64}\Rightarrow \\ $$$${a}\left({a}+{K}_{{x}} −\sqrt{\mathrm{3}}{K}_{{y}} \right)=\mathrm{39}\:\left(\mathrm{2}\right) \\ $$$${Eq}.\:{of}\:\left({K},\:{r}=\mathrm{10}\right)\:{at}\:{E}:\:\left({E}_{{x}} −{K}_{{x}} \right)^{\mathrm{2}} +\left({E}_{{y}} −{K}_{{y}} \right)^{\mathrm{2}} =\mathrm{10}^{\mathrm{2}} \:\Rightarrow \\ $$$$\left({a}+\frac{{a}}{\mathrm{2}}−{K}_{{x}} \right)^{\mathrm{2}} +\left(\frac{{a}\sqrt{\mathrm{3}}}{\mathrm{2}}−{K}_{{y}} \right)^{\mathrm{2}} =\mathrm{100}\:\Rightarrow \\ $$$${a}\left(\mathrm{3}{a}−\mathrm{3}{K}_{{x}} −\sqrt{\mathrm{3}}{K}_{{y}} \right)=\mathrm{75}\:\left(\mathrm{3}\right) \\ $$$$\left(\mathrm{1}\right)\left(\mathrm{2}\right)\left(\mathrm{3}\right)\:\Rightarrow{a}=\mathrm{8}.\mathrm{357297} \\ $$$${K}_{{x}} =\mathrm{3}.\mathrm{101745},\:{K}_{{y}} =\mathrm{3}.\mathrm{921629} \\ $$$${CK}=\sqrt{\left({K}_{{x}} −{C}_{{x}} \right)^{\mathrm{2}} +\left({K}_{{y}} −{C}_{{y}} \right)^{\mathrm{2}} }\:\Rightarrow{CK}=\mathrm{11} \\ $$

Commented by nikif99 last updated on 12/Feb/23

Commented by Mingma last updated on 12/Feb/23

Excellent

Answered by HeferH last updated on 12/Feb/23

Commented by HeferH last updated on 12/Feb/23

Commented by HeferH last updated on 12/Feb/23

where x is the height of the triangle with sides   a, 8, 5

$${where}\:{x}\:{is}\:{the}\:{height}\:{of}\:{the}\:{triangle}\:{with}\:{sides} \\ $$$$\:{a},\:\mathrm{8},\:\mathrm{5} \\ $$

Commented by Rupesh123 last updated on 13/Feb/23

Excellent!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com